PENINGKATAN HASIL BELAJAR MATEMATIKA MATERI VOLUME TABUNG MELALUI PENDEKATAN OPEN-ENDED PADA SISWA MTS TERPADU KOTA LANGSA - Azizah, Azizah (Al-Khawarizmi, 2019)
The research objective was to determine the improvement of student learning outcomes in mathematics learning through the adoption of an open-end approach in class IX-A Integrated MTs of Langsa City even semester 2018/2019. By using classroom action research, because this research was conducted to solve learning problems in class through cycles of plans, actions, observations and reflections. The results of this study indicate that the open-ended approach has a positive impact in improving learning outcomes on the tube volume material in learning mathematics. This can be seen from the better understanding of students of the material delivered by the teacher (mastery learning increases from the first and second cycles), namely respectively 62% and 94%. In the second cycle classical student mastery learning has been achieved.